2018
DOI: 10.1177/0194599818779049
|View full text |Cite
|
Sign up to set email alerts
|

Association between Eosinophilic Esophagitis and Esophageal Food Impaction in the Pediatric Population

Abstract: Objectives (1) To describe the presentation, management, and outcomes associated with pediatric esophageal food impaction (EFI) at a single tertiary care institution. (2) To identify the key clinical features of pediatric EFI that are associated with a diagnosis of eosinophilic esophagitis (EoE). Study Design Case series with chart review. Setting Tertiary care children's hospital. Subjects and Methods Thirty-five children <18 years of age presenting with EFI between November 1, 2006, and October 31, 2013, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
5
8
0
2
Order By: Relevance
“…12 Our results indicate that the presence of furrows and/or rings in EoE patients is a strong predictor of esophageal food impaction and this population should be treated more aggressively to prevent complications. Our ndings are consistent with a pediatric study showing that the presence of furrows is associated with food impaction, 13 no similar study was found in adult population.…”
Section: Discussionsupporting
confidence: 88%
“…12 Our results indicate that the presence of furrows and/or rings in EoE patients is a strong predictor of esophageal food impaction and this population should be treated more aggressively to prevent complications. Our ndings are consistent with a pediatric study showing that the presence of furrows is associated with food impaction, 13 no similar study was found in adult population.…”
Section: Discussionsupporting
confidence: 88%
“…In adolescents, the most common symptoms are dysphagia, heartburn, food impaction and chest pain. The prevalence of EoE among EGDS performed in children with esophageal food impaction and/or dysphagia is high (63-88%) [ 70 - 72 ], so children with these presenting symptoms should be rapidly tested with EGDS and multiple esophageal biopsies. A study [ 43 ] evidenced an increasing prevalence of EoE in patients with dysphagia; moreover, they were more likely to have higher eosinophils peak mucosal counts.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Gastro-esophageal reflux disease symptoms or vomiting were reported in young children with EoE, whereas older children developed dysphagia and food impaction [3]. In the study of Ettyreddy et al [42] EoE was the most frequent cause for food impaction (in more than 70% of cases).…”
Section: Clinical Manifestationsmentioning
confidence: 96%